DNA Repair Endonucleases: Physiological Roles and Potential as Drug Targets. (August 2015) - Doherty, Rachel; Madhusudan, Srinivasan
Genomic DNA is constantly exposed to endogenous and exogenous damaging agents. To overcome these damaging effects and maintain genomic stability, cells have robust coping mechanisms in place, including repair of the damaged DNA. There are a number of DNA repair pathways available to cells dependent on the type of damage induced. The removal of damaged DNA is essential to allow successful repair. Removal of DNA strands is achieved by nucleases. Exonucleases are those that progressively cut from DNA ends, and endonucleases make single incisions within strands of DNA. This review focuses on the group of endonucleases involved in DNA repair pathways, their mechanistic functions, roles in cancer development, and how targeting these enzymes is proving to be an exciting new strategy for personalized therapy in cancer.